Association of type XI collagen genes with chronic Achilles tendinopathy in independent populations from South Africa and Australia. Issue 9 (27th April 2013) - Hay, Melanie; Patricios, Jon; Collins, Robert; Branfield, Andy; Cook, Jill; Handley, Christopher J; September, Alison V; Posthumus, Michael; Collins, Malcolm
Abstract : Background: Type XI collagen, which is expressed in developing tendons and is encoded by the COL11A1, COL11A2 and COL2A1 genes, shares structural and functional homology with type V collagen, which plays an important role in collagen fibril assembly. We investigated the association of these three polymorphisms with Achilles tendinopathy (AT) and whether these polymorphisms interact with COL5A1 to modulate the risk of AT. Methods: 184 participants diagnosed with chronic AT (TEN) and 338 appropriately matched asymptomatic controls (CON) were genotyped for the three polymorphisms. Results: Although there were no independent associations with AT, the TCT pseudohaplotype constructed from rs3753841 (T/C), rs1676486 (C/T) and rs1799907 (T/A) was significantly over-represented (p=0.006) in the TEN (25.9%) compared with the CON (17.1%) group. The TCT(AGGG) pseudohaplotypes constructed using these type XI collagen polymorphisms and the functional COL5A1 rs71746744 (-/AGGG) polymorphism were also significantly over-represented (p<0.001) in the TEN (25.2%) compared with the CON (9.1%) group. Discussion: The genes encoding structural and functionally related type XI ( COL11A1 and COL11A2 ) and type V ( COL5A1 ) collagens interact with one another to collectively modulate the risk for AT. Although there are no immediate clinical applications, the results of this study provide additional evidence that interindividual variations in collagen fibril assembly might be an important molecular mechanism in the aetiology of chronic AT.